An Empirical Study On Analyzing A User’s Intention Towards Using Mobile Wallets; Measuring The Mediating Effect Of Perceived Attitude And Perceived Trust - et. al., Dr. Viral Bhatt, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Researchers wants to drive the impact of factors like perceived usefulness, perceived se of use, perceived benefits, perceived risk, perceived security, company image and social influence where perceived trust and perceived attitude are mediating variables determining theuser’sintention to use mobile wallet application. Here researcher measures the direct and indirect effects of various factors while also introducing and investigating the impact of categorical moderator of gender- male and female. Design/methodology/approach-An instrument has been designed under the guidance of five eminent researchers. Appropriate seven-point scale has been applied with the descriptive cross sectional research design. 314 valid responses are considered. Multiple regression and path analysis performed with SPSS and PLS-SEM analysis.In the process of developing structural model on mobile wallets, reliability, convergent and discriminant validity established. Here researcher confirmed significant direct impact of factors like: social influence, perceived usefulness, perceived ease of use, perceived benefits, perceived risk, and perceived security, company image on user’s attitude andtheir trust ultimately leads to intention to use mobile wallet application. Research also ensures the moderating effect of gender. The major limitation of this paper is that the study is conducted with regard to user’s attitude and intention towards mobile wallets in major cities of Gujarat region only. This is unique effort of researchers for developing structural model for mobile wallet application. This study will help in understanding the concept of interrelation amongst various factors directly and indirectly related to mobile wallets. This research is useful for all mobile wallet companies like Paytm, Google, Amazon to understand the intra relationships amongst the various factors of mobile wallets and ultimately help these companies to understand the attitude of mobile wallet users.